Analisis Sadd al-Zari’ah dalam Mencegah Gratifikasi: Analysis of Sadd al-Zari’ah in Preventing Gratification - Alwis Alwis; M Nasir (FAI UIM, 2024)
The main problems in this research are (1) the essence of Sadd al-Zari’ah in the study of fiqh proposals, (2) the method of application and its limitations, and (3) the analysis of Sadd al-Zari’ah on the prevalent practice of gratification. tired. This description is born from various phenomena that are quite dilemmatic, can be seen, observed, and analyzed in the dynamics of community life, especially those related to legal imposition in muamalah problems. This type of research is descriptive qualitative. The data source is literature. The approach used is normative theological. While processing and data analysis techniques with critical analysis. The results of this study indicate that the essence of Sadd al-Zari’ah is to prevent and block roads that are permissible but can lead to something that is haram, so that mukallaf can carry out the command shar'i or abandon the prohibition of Sha r'i in a perfect manner. The implication is that by understanding the Sadd al-Zari’ah rule, a mukallaf can avoid gratification, either as a recipient or a giver and will be wiser in concluding legal answers by studying the Shari'a texts and their meanings. Legal experts on the other hand are demanded to be wiser in responding to the problems of the ummah, especially those concerning public needs, as the practice of the principle of “rejecting bad is prioritized over achieving good”.